Is Underconfidence Favored over Overconfidence? An Experiment on the Perception of a Biased Self-Assessment - Carmen Thoma (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2013)
This paper reports findings of a laboratory experiment, which explores how elfassessment regarding the own relative performance is perceived by others. In particular, I investigate whether overconfident subjects or underconfident subjects are considered as more likable by others, and who of the two is expected to achieve a higher performance in a real effort task. I observe that underconfidence beats overconfidence in both respects. Underconfident subjects are rewarded significantly more often than overconfident subjects, and are significantly more often expected to win the competitive real-effort task. It seems as if subjects being less convinced of their performance are taken as more congenial and are expected to be more ambitious to improve, whereas overconfident subjects are rather expected to rest on their high beliefs. While subjects do not anticipate the stronger performance signal of underconfidence, they anticipate its higher sympathy value. The comparison to a non-strategic setting shows that men strategically deflate their self-assessment to be rewarded by others. Women, in contrast, either do not deflate their self-assessment or do so even in non-strategic situations, a behavior that might be driven by nonmonetary image concerns of women.
urn:nbn:de:bvb:19-epub-17460-5
Keywords: C91; D03; J16; 330; Self-confidence; Overconfidence; Experiment